PEMBUATAN PROFIL DUKUH SENTONO - Lail, Jamalul (AJIE (Asian Journal of Innovation and Entrepreneurship), 2015)
Sentono is promoted as a center for Agro Techno Park development. For support this programm, it is needed to be made profil of village’s development. Profil is made in book and digital, so the infromation is easy and fast to find.